Menguji Kenegarawanan Hakim Konstitusi Melalui Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 - Gusman, Delfina (Faculty of Law, Andalas University, 2023)
Constitutional Justice Saldi Isra's confusion in expressing a different opinion (dissenting opinion) regarding the ruling of the Constitutional Court Number 90/PUU-XXI/2023, opening up public space to question the material aspects of the decision. According to Saldi Isra, the substance of the petition in Case Number 90/PUU-XXI/2023 is simple and clearly visible.opened legal policyIn fact, it was taken over and used as a